An Investigation Into the Effects of Pressure Oscillations on Airway Smooth Muscle in Chronic Asthma - Roos, Kevin Lamar Turepu (Auckland University of Technology, 2018)
The hyperconstriction of airway smooth muscle (ASM) is the main driving mechanism during an asthmatic attack. The airway lumen is reduced, resistance to airflow increases, and normal breathing becomes more difficult. The tissue contraction can be temporarily relieved by using bronchodilator drugs which induce relaxation of the constricted airways. With one of the highest prevalence rates in the world, New Zealand’s costs for asthma treatments total an estimated NZD$825 million per year. While widely used in asthma therapies, pharmacological treatments vary in their effectiveness from one subject to another, as do the side effects of long-term usage. Studies have shown that application of mechanical oscillations which are equivalent to the physiological patterns of normal breathing and deep inspirations in healthy airways can induce airway relaxation. This type of relaxation response is not observed in asthmatics. Utilizing length oscillations (arising from positive pressure) in association with breathing patterns provides non-pharmacological options for augmenting treatment of the ASM hyperconstriction which is present in many respiratory diseases such as asthma. There is currently little known about the effects of applying superimposed pressure oscillations in combination with breathing patterns to healthy and asthmatic airways during an asthmatic attack. Results from in vivo studies of a chronic murine asthmatic model indicate that the use of superimposed pressure oscillations (SIPO) over normal breathing patterns facilitates relaxation during an induced asthmatic attack in healthy and asthmatic subjects. Oscillation patterns, physiological pressure equivalents, and their effects on key respiratory parameters are presented. Comparisons of healthy and asthmatic lung resistance (RL) and dynamic compliance (Cdyn) values are used as assessments of the changes in airway responses to applied mechanical pressure oscillations. Additionally, a standard respiratory constant is used to normalize acute and chronic asthmatic models’ data. Use of the constant assists in modeling the effects of SIPO by transforming RL and Cdyn data into Work and Power equivalents for use in interpreting ASM mechanics.
Keywords: Mechanical oscillations; Superimposed pressure oscillations; Airway smooth muscle; Breathing; Contraction; Relaxation; Resistance; Compliance